1996
DOI: 10.1136/adc.74.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular cytogenetic (FISH) diagnosis of Williams syndrome.

Abstract: Sixteen children and adolescents with a firm clinical diagnosis of Williams syndrome were investigated with the chromosome fluorescence in situ hybridisation (FISH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…Recent studies have indicated the prevalence of elastin gene deletion along with tightly linked markers in classical WS ranging from 75% to nearly 100% (12)(13)(14)(15)(16)(17)(18). The deletion breakpoints occur at duplicated regions of sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the prevalence of elastin gene deletion along with tightly linked markers in classical WS ranging from 75% to nearly 100% (12)(13)(14)(15)(16)(17)(18). The deletion breakpoints occur at duplicated regions of sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11] Because the gene encoding elastin is deleted in nearly all cases of WS, screening with a fluorescent in situ hybridization (FISH) probe for this gene deletion has become the diagnostic test of choice. 6,8,[12][13][14][15] Infantile hypercalcemia has been reported for ϳ15% of infants and children with WS. 16 The hypercalcemia in infancy usually occurs in the first years of life, resolving in most cases by 4 years of age, but it may recur during puberty.…”
mentioning
confidence: 99%
“…Hemizygosity for the elastin gene was identified using FISH (fluorescence in-situ hybridization) with the LSI Williams Syndrome Region DNA probe (VYSIS®) (Figures 1, 2, and 3a,b) as described elsewhere. 11 We also performed a meta-analysis of 11 studies selected from the literature to establish the clinical features that are associated with FISH-positive patients; these studies were those of Borg et al (1995), 12 Brewer et al (1995), 13 Kotzot et al (1995), 14 Lowery et al (1995), 15 Nickerson et al (1995), 16 Joyce et al (1996) 17 , Perez Jurado et al (1996), 18 Brondum-Nielsen et al (1997), 19 Elcioglu et al (1998); 20 Mila et al (1999), 21 and Beust et al (2000). 22 A total of 597 patients with WS were analyzed (including 20 patients of our sample), and among them, 361 individuals had the microdeletion of the ELN locus.…”
Section: Methodsmentioning
confidence: 99%